Effect of exhaust air recirculation on the operation of air handling units with heat recovery from exhaust air - Przydróżny, Edward; Szczęśniak, Sylwia (Instal, 2021)
The article presents temperature variation and system efficiency: heat recovery-recirculation of exhaust air for two typical air handling units (AHUs) configuration used nowadays in Poland. The selection of the proper AHU configuration is critical from the perspective of energy consumption neccesary for fresh air treatment. In light of the ever-increasing energy requirements for AHU's, consideration of the configuration of the units is very important and should not be shaped by equipment manufacturers, but by conscious designers of ventilation and air conditioning systems.
Keywords: heat recovery efficiency; central ventilation; air energy obtaining